2020
DOI: 10.1002/cmdc.202000460
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antitrypanosomal Activity of 1,4‐Disubstituted Triazole Compounds Based on a 2‐Nitroimidazole Scaffold: a Structure‐Activity Relationship Study

Abstract: Chagas disease affects 6–8 million people worldwide, remaining a public health concern. Toxicity, several adverse effects and inefficiency in the chronic stage of the disease are the major challenges regarding the available treatment protocols. This work involved the synthesis of twenty‐two 1,4‐disubstituted‐1,2,3‐triazole analogues of benznidazole (BZN), by using a click chemistry strategy. Analogues were obtained in moderate to good yields (40‐97 %). Antitrypanosomal activity was evaluated against the amasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…In this area, the 3-nitro-1 H -1,2,4-triazole is a relevant scaffold considering the discovery of new antichagasic agents. Moreover, studies reported that 3-nitrotriazoles derivatives showed increased potency and lower toxic effects than 2-nitroimidazole. ,, In a previous study, our research group synthesized 22 2-nitroimidazole-triazole compounds derivatives of BZN with potent antitrypanosomal activity in vitro. Bioisosterism between the amide group of the BZN scaffold and the triazole core enhanced the antichagasic activity of this series, pointing out the compound 14 , which was 6-fold more active than BZN (IC 50 = 0.65 μM) . These findings boosted our interest in broadening the structure–activity relationship (SAR) studies with triazole derivatives.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…In this area, the 3-nitro-1 H -1,2,4-triazole is a relevant scaffold considering the discovery of new antichagasic agents. Moreover, studies reported that 3-nitrotriazoles derivatives showed increased potency and lower toxic effects than 2-nitroimidazole. ,, In a previous study, our research group synthesized 22 2-nitroimidazole-triazole compounds derivatives of BZN with potent antitrypanosomal activity in vitro. Bioisosterism between the amide group of the BZN scaffold and the triazole core enhanced the antichagasic activity of this series, pointing out the compound 14 , which was 6-fold more active than BZN (IC 50 = 0.65 μM) . These findings boosted our interest in broadening the structure–activity relationship (SAR) studies with triazole derivatives.…”
Section: Introductionmentioning
confidence: 70%
“…Remarkably, analog 15ab (R 1 = Ph-4-O-Ph, IC 50 = 0.07 μM) stands out as the most promising compound of this series, demonstrating exceptional antichagasic activity in vitro at submicromolar concentrations. Specifically, this analog showed 88-fold greater activity compared to the reference drug BZN and up to 94-fold more active than the 2-nitroimidazoletriazole derivative with the same substitution pattern, 54 and still 19-fold more active than 15a. Hence, the analog 15ab (R 1 = Ph-4-O-Ph) scored an impressive selectivity index (SI > 714.20) compared to BZN (SI = 8.13) on LLC-MK2 cells.…”
Section: ■ Chemistry Remarksmentioning
confidence: 91%
See 1 more Smart Citation
“…The bioisosteric replacement between amide bonds and 1,4-disubstituted 1,2,3-triazole provides new analogues of benznidazole with anti-trypanosomal activity [ 111 ]. These compounds were synthesized by CuAAC and designed as a Craig-plot (two-dimensional plot) and Topliss Scheme (decision-making tree).…”
Section: 123-triazoles In Other Mimeticsmentioning
confidence: 99%
“…Our research group has experience synthesizing small bioactive molecules using different medicinal chemistry approaches, such as bioisosterism and molecular hybridization. Our synthesis strategy is most often inspired by natural products, such as tetrahydrofuran neolignans, whose privileged scaffold offer versatility for diverse biological applications. ,, Grandisin (Figure , compound 5 ), a neolignan obtained from Virola surinamensis, a plant commonly found on the banks of the Amazon River, possesses anti-inflammatory and antioxidant properties. Carvalho and colleagues (2010) demonstrated that grandisin reduced inflammation in formalin-induced and croton-oil-induced paw and ear edema, respectively .…”
Section: Introductionmentioning
confidence: 99%